2017
DOI: 10.3126/nje.v7i2.17975
|View full text |Cite
|
Sign up to set email alerts
|

Fungal keratitis: study of increasing trend and common determinants

Abstract: Fungal keratitis is one of the leading cause of ocular morbidity. Fungal keratitis possesses a clinical challenge due to its slow pathologic process, overlapping features, diagnostic difficulty, and potential complications. Its increasing trend can be attributed to the use of contact lens, non-judiciary corticosteroid, and vegetative trauma. Early diagnosis and treatment is the cornerstone for its effective control. Knowledge of pathological course and clinical characteristics of fungal keratitis will definite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 45 publications
2
49
1
3
Order By: Relevance
“…2 In a study from Nepal by Yogesh Acharya et al Aspergillus species, Fusarium species and Candida species are some of the common etiological agents for fungal keratitis. 22 In another study by Gopinathan U et al from South India fungal cause of keratitis was 95.4% which is much higher than present study. 23 Microbial Keratitis is a significant health problem and the differences seen in the number of cases is due to variety of predisposing factors such as contact lens users, trauma due to vegetative matter, injury, foreign body or insects, steroid use, underlying diseases such as diabetes to name a few.…”
Section: Discussioncontrasting
confidence: 54%
“…2 In a study from Nepal by Yogesh Acharya et al Aspergillus species, Fusarium species and Candida species are some of the common etiological agents for fungal keratitis. 22 In another study by Gopinathan U et al from South India fungal cause of keratitis was 95.4% which is much higher than present study. 23 Microbial Keratitis is a significant health problem and the differences seen in the number of cases is due to variety of predisposing factors such as contact lens users, trauma due to vegetative matter, injury, foreign body or insects, steroid use, underlying diseases such as diabetes to name a few.…”
Section: Discussioncontrasting
confidence: 54%
“…Additionally, we confirmed that ATF4 expression was upregulated with the addition of A. fumigatus conidia both in HCECs and THP-1 macrophages at 16 hours after stimulation. Fungal keratitis is often caused by ocular trauma resulting from eye irritation by vegetative matter [1, 25]. From an anatomical point of view, the epithelium is one of the earliest corneal structures to come in contact with pathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The incidences of keratitis account for an estimated 930,000 visits to the doctor's office and outpatient clinics and *58,000 emergency department visits with *76.5% of the keratitis visits requiring drug prescriptions. [2][3][4][5] Episodes of keratitis and other ocular corneal infections led to an estimated $175 million in direct health care expenditures in the United States annually, including $58 million for Medicare patients and $12 million for Medicaid patients, according to an analysis by Collier et al in Morbidity and Mortality Weekly Report for the Centers for Disease Control and Prevention. 2,3,5 The polyene and azole antifungals have been the mainstay in the pharmacotherapy of invasive systemic fungal infections due to their broad antifungal spectrum and potent biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Episodes of keratitis and other ocular corneal infections led to an estimated $175 million in direct health care expenditures in the United States annually, including $58 million for Medicare patients and $12 million for Medicaid patients, according to an analysis by Collier et al in Morbidity and Mortality Weekly Report for the Centers for Disease Control and Prevention. 2,3,5 The polyene and azole antifungals have been the mainstay in the pharmacotherapy of invasive systemic fungal infections due to their broad antifungal spectrum and potent biological activity. 6,7 The polyene class, comprising amphotericin B, nystatin, and natamycin, has been widely used in therapy ow-ing to the antifungal activity against Candida spp., Aspergillus spp., Fusarium spp., Scedosporium spp., and Zygomycetes classes of fungi, which are the common causative species for fungal infections.…”
Section: Introductionmentioning
confidence: 99%